Knowledge and awareness on HIV/AIDS among blood donors: A study in Rajshahi, Bangladesh - Md. Abdul Goni; Md. Mahfuzur Rahman (Universiti Kebangsaan Malaysia, 2012)
HIV/AIDS is the most devastating disease that mankind has ever faced. For being neighboring country of India, Bangladesh has been highly vulnerable to HIV infection. Although Bangladesh continues to maintain low HIV prevalence status, the infection rate is on the rise in Rajshahi Division. Some studies have been carried out on the knowledge about HIV/AIDS among some risk groups, but studies on blood donor’s awareness about HIV/AIDS are rarely found. This study aims at investigating the knowledge and awareness about HIV/AIDS among the blood donors in Rajshahi Metropolitan of Bangladesh. Methods In this study, primary data was used. The data was collected by the authors during the period 3rd March to 28th April in 2008. Purposive sampling technique has been applied. Interview method has been used to collect information from the respondents. Results Data reveals that, though 89 percent blood donors knew it is transmitted through blood transfusion, only 1 percent of them had undertaken blood test before donation, which is alarming. The odds of having preliminary and preventive knowledge reduce with the increase in age of the respondents. Besides these, blood donors who were educated and who were in service were found to be more aware about the HIV/AIDS than the others. Conclusions Strict rules and regulations should be maintained regarding blood screening. Overall people should be encouraged to use condoms and abide by the religious rules to avoid HIV/AIDS infection. Both Government and Non- Government organizations should augment their educational and Focused Group Discussion (FGD) programs on HIV/AIDS knowledge.